Liberating co-ops a guide to creating women friendly and gender-responsive co-ops in the Philippines. (Asian Women in Co-operative Development Forum, 1998)
A guiding tool that instructs how to transform gender awareness into action for use by co-ops who wish to address gender inequality in their organization. A companion material "Liberating Co-ops, Stories of Women Friendly and Gender-Responsive Co-operatives in the Philippines" contains stories that show the effects of actions taken from this book.